An ocean free of nuclear weapons? Regional security governance in the South Atlantic - Mattheis, F.; Seabra, P. (Politics and Governance, 2022)
Even though oceans are pivotal for the non-proliferation of nuclear weapons, they constitute a blind spot in the global non-proliferation regime. This article analyses how regional security governance mechanisms may fill such gaps by bringing a maritime focus to non-proliferation studies. With three nuclear-weapons-free zones and one zone of peace surrounding or covering its maritime space, the South Atlantic serves as an illustrative case to understand the provision of security governance for the seas. The article identifies a range of legal, political, and practical challenges that can impede regional initiatives from achieving security sovereignty over maritime spaces. However, while non-proliferation might remain precarious, these mechanisms are not without success, as they serve to establish the opposition to nuclear weapons as a recognised norm, both at the UN level and among the Global South. The narrative of non-proliferation also allows regional states to justify the pursuit of security objectives. The article concludes by outlining the conditions for regional maritime governance to become more effective in terms of non-proliferation.